O6.7. TESTING THE HIGH RISK AND TRANSITION FRAMEWORK IN THE GENERAL POPULATION: POPULATION-BASED MEASURES OF RISK AND TRANSITION FOR PSYCHOSIS 6-YEAR LONGITUDINAL FOLLOW-UP. (9th April 2019) - Pries, Lotta-Katrin; Guloksuz, Sinan; Have, Margreet Ten; Graaf, Ron de; Dorsselaer, Saskia van; Rutten, Bart P F; Os, Jim Van
Abstract: Background: Early intervention of psychosis is an active area of investigation. Guided by the ultra-high-risk framework, clinical research has thus far focused largely on the positive psychotic symptoms. However, findings from the general population—and recently from clinical samples such as Headspace Australia— suggest that psychotic symptoms might be bidirectionally and non-causally associated with the severity of multidimensional psychopathology and indicate poor outcome. Data on progression of psychotic symptoms in the general population are scarce. Therefore, in this longitudinal study, we aimed to explore the "risk" and "transition" in the general population by evaluating the incidence and transition rates in different categorical risk states with a focus on the presence and severity of psychotic experiences (PE), estimating the population attributable fraction of transition (PAF; the proportion of transition that would not have occurred when the risk was decreased), and assessing preceding affective symptomatology. Methods: Data (n = 6071) from three waves of the Netherlands Mental Health Survey and Incidence Study-II (NEMESIS-II), a prospective survey in the Dutch general population aged 18 – 64, was used. Participants with life-time diagnosis of schizophrenia and related disorders at baseline were excluded. The baseline data (T0) of NEMESIS-II were collected from 2007 to 2009 and were followed up at year 3 (T1) and year 6 (T2). PE were assessed with a modified version (i.e. 20 items with "yes" vs "no" responses) of the CIDI 1.1; and later confirmed by a clinician on telephone interview. The categorical risk strata were defined as no risk (No PE), low-risk (single PE), moderate-risk (multiple PE), and high-risk (at least 1 PE + help seeking behaviour). Transition to psychosis was defined as antipsychotic treatment or clinical admission for psychotic symptoms. Results: The incidence rates were low across the study period (low-risk: 0.9%, moderate-risk: 0.3%, high-risk: 0.5%, and transition to psychosis: 0.07%), with low annual transition rates (no-risk: 0.03%, low-risk: 0.1%, moderate-risk: 0.1%, high-risk:1.2%). The PAF was 7% for the low-risk, 3% for the moderate-risk, and 49% for the high-risk strata. Preceding affective symptomatology was frequent in all risk states and increased as a function of the risk strata: no-risk (55%), low-risk (75%), moderate-risk (77%), high-risk (90%), and psychosis transition (97%). Discussion: Although individuals at high-risk are more likely to transition and almost half of those cases could be prevented if risk is successfully eliminated, low incidence and transition rates indicate that the high-risk approach would have a low public health impact in the general population. Our findings showing frequent preceding affective symptomatology also suggest that shifting the focus to multidimensional psychopathology may add valuable knowledge to preventive research.